PENERAPAN DIGITAL MARKETING MELALUI MEDIA SOSIAL DI SMK TEUKU UMAR - Ade Mardiansyah; Aldo; Damas Aryanto; Endru Yuda Muslim; Frans Liman Dibrata; Giardo Nur Alfajianzah; Irsyad Ikhsanudin; Muhamad Fauzi; Rizqi Maulana; Yudha Febriansyah (Abdi Jurnal Publikasi, 2022)
The rapid development of today's social media is caused by everyone who feels like they can "own" their own media. Social media is also not spared from the various functions that we can take, such as building relationships, opening and looking for jobs, and also doing business can also be done with social media. The most relevant business strategy in the marketing aspect uses digital tools or known as digital marketing, namely marketing methods carried out using the help of digital instruments, especially the internet along with the various applications contained therein and the equipment that supports the use of this media, which allows the creation of a network or connectedness with many parties, in this case between producers/sellers and customers, without being limited by distance, time, and place. Where the purpose of this service activity is to increase understanding of Digital Marketing, the use and also what strategies are in digital marketing. We, from the Community Service Program Team (PKM) at Pamulang University (UNPAM), consisting of 10 people, are called upon to participate in helping solve problems faced by Teuku Umar Vocational High School students by using the method of implementing digital marketing through social media.